Analisis Keragaman Pendapatan Usahatani Sayur dan Jagung Hibrida (Studi Kasus Kelompok Tani di Desa Ababi Kecamatan Abang, Kabupaten Karangasem, Provinsi Bali) - I DEWA AYU DEVI SAVITRI WIRYASTI; NI WAYAN PUTU ARTINI; NI LUH MADE INDAH MURDYANI DEWI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2022)
Vegetable and Corn Farming (Case Study: Farmer Group in Ababi Village, Abang District, Karangasem Regency, Bali Province). Hybrid vegetable and corn farming is one type of farming activity carried out by the Baja Tani group. In general, farmers do not know how much influence the type of commodity has on their farm income, therefore it is important to observe whether diversity affects their farm income. This study aims to determine the farm income of cultivated hybrid vegetables and corn, this study also aims to determine what constraints affect farming activities and maize and whether the choice of commodity types affect farm income. The results showed that the type of commodity had an effect on farm income. From the results of the ANOVA analysis, it was obtained that the F statistic value of 27,742 > 2,911 and a significance value of < 0.05 where the highest income was obtained by hybrid corn farmers compared to farmers cultivating mustard greens, long beans, and eggplant so that the farmer's choice to cultivate corn was considered appropriate. As for the obstacles faced by farmers, as many as 43% of farmer group members who originally cultivated vegetables experienced problems related to capital and farming cultivation techniques. Marketing constraints 70% of vegetable farmers experienced problems related to marketing channels because one of the vegetable distribution places, namely hotels and villas, had to close due to the pandemic. Changes in price are one of the obstacles felt by all farmers because they experience a decline in prices due to large harvests.